Mucoadhesive polymers for buccal drug delivery system: An overview - Sharma, Mukesh; Sheeba, F.R.; Yadav, Rajkumar Prasad; Patel, Akshay Kumar; Kumar, Yeshavantha (Asian Journal of Pharmaceutical Research and Development, 2021)
Pharmaceutical scientists around the globe have been seeking to discover as an alternative to injections over the last few, transdermal and transmucosal routes decades. The buccal cavity mucosa the most convenient and easily available site for the distribution of local and systemic therapeutic agents was found to be dosage forms among the numerous transmucosal sitesavailable.Theories and various polymers used in mucoadhesive drug delivery. Mucoadhesive polymers increases the residence time, prolong the absorption, enhances solubilityand dissolution characteristics of poorly soluble drugs. In addition, we are focused on the latest generation of mucoadhesion polymers, led by the latest formulation of mucoadhesive for the distribution of oral drugs, such as thiolated polymers. A good insight into mucoadhesion polymers, the mucoadhesive phenomenon and the factors that can affect polymer mucoadhesion is given in the current analysis. The systematic drug delivery has been investigated for buccal mucosa and local drug treatment or therapy is subjected to first pass metabolism. Oral mucosa drug delivery by discussing the structural features of mucosa, mechanism of mucoadhesion. General consideration in design of mucoadhesive buccal dosage forms, permeation enhancers and the various evalution method along with literature survey of the buccal mucoadhesive.